Adjusting Crystal Orientation to Promote Sodium‐Ion Transport in V5S8@Graphene Anode Materials for High‐Performance Sodium‐Ion Batteries. Issue 2 (5th January 2023) - Tang, Lin‐bo; Li, Pei‐yao; Cui, Ru‐de; Peng, Tao; Wei, Han‐Xin; Wang, Zhen‐yu; Wang, Hai‐yan; Yan, Cheng; Mao, Jing; Dai, Ke‐hua; Chen, He‐zhang; Zhang, Xia‐hui; et al.
Abstract: Sodium‐ion batteries (SIBs) have inspired the potential for widespread use in energy storage owing to the advantages of abundant resources and low cost. Benefiting from the layered structure, 2D‐layered materials enable fast interlayer transport of sodium ions and thus are considered promising candidates as anodes for SIBs. Herein, a strategy of adjusting crystal orientation is proposed via a solvothermal method to improve sodium‐ion transport at the edge of the interlayers in 2D‐layered materials. By introducing surfactants and templates, the 2D‐layered V5 S8 nanosheets are controlled to align the interlayer diffusion channels vertically to the surface, which promotes the fast transport of Na + at the edge of the interlayers as revealed by experimental methods and ab initio calculations. Benefiting from the aligned crystal orientation and rGO coating, the vertical‐V5 S8 @rGO hybrid delivers a high initial discharge capacity of 350.6 mAh g −1 at a high current density of 15 A g −1 . This work provides a strategy for the structural design of 2D‐layered anode materials by adjusting crystal orientation, which demonstrates the promise for applications in fast‐charging alkaline‐ion batteries. Abstract : In this study, a strategy of adjusting crystal orientation is proposed to improve sodium‐ion transport at the edge of the interlayers in two‐dimensional (2D)‐layered materials. The 2D‐layered V5S8 nanosheets are controlled to align the interlayer diffusion channels vertical to the surface, which promotes the fast transport of Na + at the edge of the interlayers.